Morphological Description and Ethnobotanical Review of the Orphan Crop Myin-Hkwa (Centella asiatica L.) From Myanmar - Shukurova, Musavvara Khaitovna; Myint, Daisy; Yi, San San; Saw, Ohm Mar; Watanabe, Kazuo N. (Frontiers in Sustainable Food Systems, 2021)
The use and trade of medicinal plants in Asia and South East Asia countries are poorly known due to limited studies. Centella asiatica represented from Myanmar is one of the underutilized orphan crop, commonly known as Asiatic pennywort or Gotu kola. It is claimed to utilize as a folk medicine to cure a variety of both mild and chronic diseases due to possessing anti-rheumatic, antipyretic, diuretic, anti-bacterial, antiviral, and anti-inflammatory effects, for neural condition, and as a mental rejuvenator. The species is distributed worldwide through the tropics and subtropics, but its recognition is rather orphaned. It is a perennial flowering plant with leaves and stems that can be consumed as a green leaf vegetable due to its nutritional value. The objective of the current article was a morphological characterization of C. asiatica plant origin from Myanmar but grown in Japan. According to conducted morphological characterization, C. asiatica plants growing under different environmental conditions displayed phenotypic differences. This may affect the medicinal and nutritional properties of this plant. Besides, we brought a brief review of its ethnobotanical uses.